2000
DOI: 10.1097/00007435-200003000-00011
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Asymptomatic STDs in Incarcerated Minority Male Youth

Abstract: The findings indicate an urgent need for routine STD screening and STD-prevention programs for adolescent males in detention facilities. A study of 284 detained black male adolescents revealed 18% prevalence of gonorrhea, chlamydia, or both. Approximately 84% of those with sexually transmitted diseases self-reported not having symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 9 publications
3
59
0
Order By: Relevance
“…If symptoms occur, they usually occur within one to three weeks after exposure [5]. Symptomatic patient may have discharge from penis/vagina or dysuria; burning and itching around the genital opening and inflammation of the testicles [6,7]. In a single Chlamydia infection there is a 25% chance of sterility, 50 % with a second infection and almost guarantees sterility in third due to pelvic inflammatory disease (PID) [8].…”
Section: Introductionmentioning
confidence: 99%
“…If symptoms occur, they usually occur within one to three weeks after exposure [5]. Symptomatic patient may have discharge from penis/vagina or dysuria; burning and itching around the genital opening and inflammation of the testicles [6,7]. In a single Chlamydia infection there is a 25% chance of sterility, 50 % with a second infection and almost guarantees sterility in third due to pelvic inflammatory disease (PID) [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent evidence from the Centers for Disease Control and Prevention indicated that rates of gonorrhea among adolescent detainees were almost 7 and 10 times greater among these males and females, respectively, when compared to adolescents from the general population (Center for Disease Control and Prevention, 2002). Furthermore, surveillance surveys have consistently shown that detained adolescents have high rates of chlamydia and gonorrhea infection than other adolescent groups (Canterbury et al, 1995;Pack, DiClemente, Hook & Oh, 2000). Unfortunately, the pathways to such behaviors are not sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 90% of infected men [7][8][9][10][11][12] and women [7][8][9] are asymptomatic. Therefore, most infections will be detected only through routine screening.…”
mentioning
confidence: 99%